Indigenous Bacteria Have High Potential for Promoting Salix integra Thunb. Remediation of Lead-Contaminated Soil by Adjusting Soil Properties - Niu, Xiaoyun; Zhou, Jian; Wang, Xiaona; Su, Xiaoyu; Du, Shaohua; Zhu, Yufei; Yang, Jinyu; Huang, Dazhuang (Frontiers in Microbiology, 2020)
Salix integra Thunb., a fast-growing woody plant species, has been used for phytoremediation in recent years. However, little knowledge is available regarding indigenous soil microbial communities associated with the S. integra phytoextraction process. In this study, we used an Illumina MiSeq platform to explore the indigenous microbial composition after planting S. integra at different lead (Pb) contamination levels: no Pb, low Pb treatment (Pb 500 mg kg-1), and high Pb treatment (Pb 1500 mg kg-1). At the same time, the soil properties and their relationship with the bacterial communities were analyzed. The results showed that Pb concentration was highest in the root reaching at 3 159.92±138.98 mg kg-1 under the high Pb treatment. Planting S. integra decreased the total Pb concentration by 84.61 mg kg-1 and 29.24 mg kg-1, and increased the acid-soluble Pb proportion by 1.0 % and 0.75 % in the rhizosphere and bulk soil under the low Pb treatment compared with unplanted soil, respectively. However, it occurred only in the rhizosphere soil under the high Pb treatment. The bacterial community structure and microbial metabolism were related to Pb contamination levels and planting of S. integra, while the bacterial diversity was only affected by Pb contamination levels. The dominant microbial species were similar, but their relative abundance shifted in different treatments. Most of the specific bacterial assemblages whose relative abundances were promoted by root activity and/or Pb contamination were suitable for use in plant-microbial combination remediation, especially many genera coming from Proteobacteria. Redundancy analysis (RDA) showed available nitrogen and pH having a significant effect on the bacteria relating to phytoremediation. The results indicated that indigenous bacteria have great potential in the application of combined S. integra-microbe remediation of lead-contaminated soil by adjusting soil properties.